The design of a semantic differential scale for measuring the psychosocial well-being of students - Viljoen, Marianne (Acta Academica: Critical views on society, culture and politics, 2012)
This article describes the construction and standardisation of a semantic differential scale for measuring and quantifying the psychosocial well-being of students. The respondents rate the following aspects of their childhood years: emotional support while growing up, socio-economic background, whether they grew up in an environment conducive to learning, and the presence of depression in the family. Regarding the students’ current life situation, the scale measures the degree of relationship and economic problems experienced by the students, the presence of depression, and concerns regarding HIV and AIDS.